Student’s Mental Health and the Indian Legal Framework: A Study (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Student mental health has emerged as a critical concern in India, exacerbated by academic pressures, social stigma, and inadequate support systems. This study explores the Indian legal framework's role in addressing mental health challenges among students, positioning mental well-being as a fundamental human right enshrined in constitutional provisions and international obligations.Key focus areas include an overview of prevalent mental health issues in Indian educational institutions, the evolution of relevant laws such as the Mental Healthcare Act, 2017, and policies like the National Mental Health Policy. It examines institutional responsibilities, including the duty of care owed by universities and schools, and mandatory counseling.The analysis reveals significant gaps in implementation, such as fragmented policy enforcement, limited resources, and judicial reluctance in recognizing student-specific rights. Challenges include overburdened counseling services and cultural barriers to seeking help.Arguing for a rights-based approach, the study proposes comprehensive reforms: mandatory mental health curricula, robust accountability mechanisms for institutions, and integration of mental health into education laws. These recommendations aim to foster a supportive ecosystem, ensuring student well-being aligns with legal imperatives for holistic development.